Challenges and Adaptation Practices of Farmers on Climate Change - Tuble, Ruvy; Lacuesta, Leni (Journal of Interdisciplinary Perspectives, 2024)
Climate change presents the agricultural industry with unforeseen difficulties, impacting livelihoods, food security, crop productivity, and sustainability. This descriptive study aims to illuminate the prevalent challenges in production and cropping patterns experienced by farmers due to climate change, along with their primary adaptation practices to mitigate adverse effects. It employs statistical tools such as ranking, mean, standard deviation, frequency count, and percentage distribution for data analysis. The respondents primarily consisted of high school graduate women with extensive farming experience and land ownership. Results indicate that climate change has exacerbated challenges in crop production, with low yields, pest and disease outbreaks, and flood damage being the most prominent issues. Farmers encounter numerous challenges in deciding on cropping patterns, mainly due to limited knowledge about viable techniques such as crop mapping, intercropping, pest and nutrient management, and water scarcity in non-irrigated fields. The results also show that farmers have adopted several strategies, including reducing the use of pesticides and petroleum-based fertilizers, conserving water during dry seasons, and improving drainage and soil mulching to prevent weed growth. Interestingly, indigenous methods have also been continuously utilized to mitigate the effects of climate change. This emphasizes the importance of innovative farming methods and ongoing farmer education initiatives for capacity building. Additionally, the results found no statistically significant association between challenges and adaptation practices.